2007
DOI: 10.1073/pnas.0703192104
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen metabolism and reactive oxygen species cause chromosomal rearrangements and cell death

Abstract: The absence of Tsa1, a key peroxiredoxin that functions to scavenge H2O2 in Saccharomyces cerevisiae, causes the accumulation of a broad spectrum of mutations including gross chromosomal rearrangements (GCRs). Deletion of TSA1 also causes synthetic lethality in combination with mutations in RAD6 and several key genes involved in DNA double-strand break repair. In the present study we investigated the causes of GCRs and cell death in these mutants. tsa1-associated GCRs were independent of the activity of the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 48 publications
7
71
0
Order By: Relevance
“…In support of this view, Tsa1 deficiency combined with deficiencies in Ogg1, a glycosylase that removes 7,8-dihydro-8-oxo-29-deoxyguanosine (8-oxo-dG; a major, mutagenic product of DNA oxidation) results in markedly elevated mutation rates (Huang and Kolodner 2005). Furthermore, the increased mutation rate in tsa1 cells is suppressed by anaerobiosis (Ragu et al 2007). However, in contrast to Ogg1-deficient cells, where the mutation rate returns to wild-type levels in the absence of oxygen (Northam et al 2010), a tsa1 mutant has a somewhat higher mutation rate than wild-type cells also in the absence of oxygen (Ragu et al 2007).…”
Section: Links Between Genome Instability Cancer and Prx Activitymentioning
confidence: 88%
See 1 more Smart Citation
“…In support of this view, Tsa1 deficiency combined with deficiencies in Ogg1, a glycosylase that removes 7,8-dihydro-8-oxo-29-deoxyguanosine (8-oxo-dG; a major, mutagenic product of DNA oxidation) results in markedly elevated mutation rates (Huang and Kolodner 2005). Furthermore, the increased mutation rate in tsa1 cells is suppressed by anaerobiosis (Ragu et al 2007). However, in contrast to Ogg1-deficient cells, where the mutation rate returns to wild-type levels in the absence of oxygen (Northam et al 2010), a tsa1 mutant has a somewhat higher mutation rate than wild-type cells also in the absence of oxygen (Ragu et al 2007).…”
Section: Links Between Genome Instability Cancer and Prx Activitymentioning
confidence: 88%
“…Furthermore, the increased mutation rate in tsa1 cells is suppressed by anaerobiosis (Ragu et al 2007). However, in contrast to Ogg1-deficient cells, where the mutation rate returns to wild-type levels in the absence of oxygen (Northam et al 2010), a tsa1 mutant has a somewhat higher mutation rate than wild-type cells also in the absence of oxygen (Ragu et al 2007).…”
Section: Links Between Genome Instability Cancer and Prx Activitymentioning
confidence: 99%
“…Several studies using this approach have demonstrated that there are eight pathways for suppressing these chromosomal aberrations, while six pathways promote GCR formation. The suppression mechanisms include cell cycle checkpoints [7][8][9][10][11][12], post-replication [13,14] and mismatch repair [15,16], recombination pathways, an anti-de novo telomere addition mechanism [17,18], chromatin assembly factors [11,19], mechanisms that prevent end-to-end chromosome fusions [17,18,20] and a pathway detoxifying reactive oxygen species [14,21,22]. In contrast, the promoters of GCRs include telomerase-related factors [17,23], a mitotic checkpoint network [24], the Rad1-Rad10 endonuclease [25], non-homologous end-joining proteins including Lig4 and Nej1 [17], a pathway generating inappropriate recombination via sumoylation and the Srs2 helicase [13] and the Bre1 ubiquitin ligase [13].…”
Section: Introductionmentioning
confidence: 99%
“…Endogenous reactive chemicals such as reactive oxygen species and certain lipid peroxidation products are thought to contribute significantly to aging, age-related degenerative diseases, and cancer (1)(2)(3)(4). Cellular DNA is one of their targets, and replication of un-repaired DNA damage introduces mutations into the genome, thereby contributing to the aforementioned biological effects.…”
mentioning
confidence: 99%